2022
DOI: 10.3389/fnut.2022.899137
|View full text |Cite
|
Sign up to set email alerts
|

Association between dried fruit intake and pan-cancers incidence risk: A two-sample Mendelian randomization study

Abstract: BackgroundObservational studies have revealed that dried fruit intake may be associated with cancer incidence; however, confounding factors make the results prone to be disturbed. Therefore, we conducted a two-sample Mendelian randomization (MR) study to explore the causal relationship between dried fruit intake and 11 site-specific cancers.Materials and methodsForty-three single nucleoside polymers (SNPs) with robust genome-wide association study (GWAS) evidence, strongly correlated with dried fruit intake, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…To further exclude bias due to weak instrumental variables, we used F -statistics to assess the presence of weak instrumental variables. F -statistics ( F -statistics = β 2 /se 2 )is an index to evaluate the weakness of IVs, since IVW could be easily affected by weak IVs, so we removed weak IVs, namely, SNPs by F -statistics ≤ 10 based on previous studies ( Zhou et al, 2019 ; Nazarzadeh et al, 2020 ; Jin et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further exclude bias due to weak instrumental variables, we used F -statistics to assess the presence of weak instrumental variables. F -statistics ( F -statistics = β 2 /se 2 )is an index to evaluate the weakness of IVs, since IVW could be easily affected by weak IVs, so we removed weak IVs, namely, SNPs by F -statistics ≤ 10 based on previous studies ( Zhou et al, 2019 ; Nazarzadeh et al, 2020 ; Jin et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…In traditional IVW regression, the intercept term in linear regression is forced to be zero, whereas the MR Egger regression estimates the intercept term in the regression equation. A statistically significant non-zero intercept term indicates the presence of directional bias in the selected genetic variants (assuming that pleiotropic effects change the effect in one direction) ( Figure 2A ) ( Jin et al, 2022 ; Xu et al, 2022 ). In most cases, IVW was used to assess causal effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A two-sample Mendelian randomization study utilized ~500,000 samples from the UK Biobank database to investigate dried fruit intake and cancer risk [ 62 ]. In this data set, for one standard deviation increase in genetically predicted dried fruit intake, a reduced risk was observed for oral cavity/pharyngeal cancer, lung cancer, squamous cell lung cancer, breast cancer, pancreatic cancer, and cervical cancer [ 62 ].…”
Section: Dried Fruits and Cancermentioning
confidence: 99%
“…Studies have shown that the consumption of dried fruit may have a protective effect against cancer. It is suggested that health education and reasonable adjustment of dietary ratios may contribute to the primary prevention of cancer ( 26 ). There is also a high-quality MR study on the association between processed meat and the risk of cancer.…”
Section: Introductionmentioning
confidence: 99%